Pharmacoeconomic Evaluation of Isoniazid and Pyridoxine Using ABC/VED Analysis - Alina Osyntseva (SSP Modern Pharmacy and Medicine, 2026)
Tuberculosis remains one of the leading infectious pathologies, the treatment of which requires long-term pharmacotherapy, significant financial resources and ensuring high adherence of patients to treatment. In modern conditions, the use of pharmacoeconomic approaches to optimize anti-tuberculosis therapy and rational use of drugs is of particular importance. One of the most effective tools for assessing the clinical and economic feasibility of drug use is combined ABC/VED analysis. The purpose of the study was to conduct a comprehensive ABC/VED analysis of the active pharmaceutical ingredients isoniazid and pyridoxine, considering the cost of the Defined Daily Dose (DDD), to assess their clinical and economic significance and justify the creation of a combination drug in TB therapy. The study materials were data from the State Register of Medicines of Ukraine, the State Formulary of Medicines of Ukraine, information on wholesale prices and DDD indicators. The study used the methods of ABC analysis, VED analysis and combined ABC/VED analysis. As a result of the ABC analysis, it was found that isoniazid forms the main share of costs in the structure of anti-tuberculosis pharmacotherapy and belongs to group A, while pyridoxine is characterized by a moderate level of costs and was assigned to group B. According to the results of the VED analysis, isoniazid is classified as a Vital component, and pyridoxine – as an Essential component of anti-tuberculosis therapy. Combined ABC/VED analysis showed that isoniazid belongs to the AV category, and pyridoxine – to the BE category, which indicates their high clinical significance at different levels of economic burden. It has been established that the combination of isoniazid and pyridoxine in the composition of the combination drug is clinically and pharmacoeconomically justified. This approach can contribute to the optimization of anti-tuberculosis pharmacotherapy, increase the safety of treatment, improve patient adherence to therapy and rationalize the costs of the health care system.